2015
DOI: 10.1039/c5ob01821h
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis and absolute stereochemistry of the proteasome inhibitors cystargolides A and B

Abstract: The absolute stereochemistry of the cystargolides was determined by total synthesis. Evaluation of synthetic cystargolides and derivatives showed that the natural (2S,3R) stereochemistry is essential for activity. Moreover, benzyl esters (−)-10 and (−)-15 were found to be about 100 times more potent, and to selectively kill MCF-7 cancerous cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Cystargolides A and B (CysA and CysB, Scheme 1a), were isolated from the actinomycete Kitasatospora cystarginea, and these compounds have been described to block human proteasome activity in the μΜ range [21]. Recently, our group accomplished the first total synthesis and determined the absolute stereochemistry for both CysA and CysB [22]. This work identified the benzyl ester 1 (Scheme 1a) as a potent analog that inhibited the proteasome at low nanomolar concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystargolides A and B (CysA and CysB, Scheme 1a), were isolated from the actinomycete Kitasatospora cystarginea, and these compounds have been described to block human proteasome activity in the μΜ range [21]. Recently, our group accomplished the first total synthesis and determined the absolute stereochemistry for both CysA and CysB [22]. This work identified the benzyl ester 1 (Scheme 1a) as a potent analog that inhibited the proteasome at low nanomolar concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…This work identified the benzyl ester 1 (Scheme 1a) as a potent analog that inhibited the proteasome at low nanomolar concentrations. Interestingly, 1 also displayed low micromolar cytotoxicity against MCF7 breast cancer cells [22], warranting further investigations of the cystargolide scaffold as a peptidic PI like the belactosins.…”
Section: Introductionmentioning
confidence: 99%
“…4 [α] 20 D +74 ( c 4.4, CHCl 3 )}, therefore, the absolute stereochemistry of natural hortonone C must be described as (6 S ,7 S ,10 S ), in agreement with the Minehan report. 5 Evaluation of cytotoxicity using the MTT assay as described previously 29 demonstrated that synthetic hortonone C (−)- 1 was not active (IC 50 >100 μM) against MCF-7 breast cancer cells, indicating that the absolute stereochemistry of the natural product is essential for activity…”
Section: Resultsmentioning
confidence: 99%
“…176 Cystargolides A (66) and B (67) exhibited inhibition towards the ChT-L site of the 20S proteasome with IC 50 values of 0.36 AE 0.017 mM and 0.93 AE 0.032 mM, respectively. The total syntheses and absolute stereochemistry of cystargolides A and B were later successfully achieved by Tello-Aburto et al 177 Wolf et al were also able to access the cystargolides and belactosins using biosynthetic methods. The stereochemistry of these natural products is integral to inhibitory activity: maintaining the (2R,3S) absolute stereochemistry contributes to potency of inhibitors.…”
Section: Rsc Chemical Biology Reviewmentioning
confidence: 99%
“…178 Benzylation of the N-terminus also improved inhibitory potency 100-fold, as evidenced by analogues 68 (IC 50 : 9.2 AE 0.59 nM) and 69 (IC 50 : 9.0 AE 1.4 nM). 177 Subsequent optimization of the cystargolide scaffold was achieved in 2018: benzyl ether 70 inhibits the hb5 subunit of Jurkat cell lysate with an IC 50 value of 3.1 AE 0.2 nM as compared to cystargolide B (IC 50 : 0.90 AE 0.11 mM), and is also cytotoxic against MCF-7 and RPMI-8226 cells. 179…”
Section: Rsc Chemical Biology Reviewmentioning
confidence: 99%